Effective software testing a developer's guide - Aniche, Maurício (Manning Publications Co., 2022)
Effective Software Testing is a hands-on guide to creating bug-free software. Written for developers, it guides you through all the different types of testing, from single units up to entire components. You'll also learn how to engineer code that facilitates testing and how to write easy-to-maintain test code. Offering a thorough, systematic approach, this book includes annotated source code samples, realistic scenarios, and reasoned explanations.
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on August 22, 2022)
Keywords: Computer programs -- Testing; Computer programs -- Development; Logiciels; Essais; Logiciels; Développement; Computer programs; Testing